HUBUNGAN KEIKUTSERTAAN SENAM PROLANIS DENGAN KETERKONTROLAN TEKANAN DARAH PADA PASIEN BPJS DI KLINIK BATAM SEHAT - Andi Ipaljri Saputra; Isramilda , (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2019)
Since 2014 BPJS Health has implemented the Chronic Disease Management Program (PROLANIS) which has a program of medical/educational consultation activities, home visits, reminders, club activities such as gymnastics and health status monitoring with the target of all BPJS health participants with chronic diseases (Diabetes Mellitus) Type 2 and Hypertension). The Batam Sehat Clinic conducted a chronic disease management program in 2015 with 154 registered patients, while BPJS patients who took part in the PROLANIS exercise in July-September 2018 totaled 155 people. This type of research is an observational analytic survey with a cross-sectional approach conducted at Batam Sehat Clinic. Data obtained by taking medical records in the form of attendance PROLANIS gymnastics with a total sampling technique that the overall number of BPJS patients who take PROLANIS exercises from July-September is 155 BPJS patients. From 155 BPJS patients, the frequency distribution of BPJS patients participating in PROLANIS and blood pressure was controlled 71 (85.5%) and uncontrolled blood pressure was 12 (14.5%). While those who did not participate in PROLANIS exercise were controlled blood pressure 32 (44.4%) and 40 (55.6%) uncontrolled blood pressure. Based on the results of statistical tests it is known that there is a correlation between the participation of PROLANIS gymnastics and blood pressure control in BPJS patients in Batam Sehat Clinic with p-value = 0,000 where p <0.05. Based on this research, it can be concluded that there is a correlation between the participation of PROLANIS gymnastics and the control of blood pressure in BPJS patients.